Potential Legal-policy and Socio-ecological Compliance Requirements on Developing Slaughterhouse in Tanzania: A Stakeholders’ Perspective - Babune, George Julius (International Journal of Scientific Research in Biological Sciences, 2022)
This paper examines the compliance requirements of slaughterhouse development on legal-policy and socio-ecological dimensions at Zuzu in Dodoma City Tanzania. It uses a 30 sample size acquired by purposive sampling procedures to implement focus group discussion of the case with a qualitative approach. It also employed 22 Key Informants, and observation methods. Results indicate that stakeholders were supporting the proposed development with concerns on liquid wastes management and treatment. Found that there would be positive and negative impacts such as direct employment of 30 human resource, liquid waste generation, sound, and noise pollution. Others would involve spread and development of Kiswahili, English, and Chinese languages. The project was supposed to implement mitigation and enhancement measures to address the stated impacts. These would include employment of the state of the art technology for waste management, and the use of protective gears for workers. It was also supposed to abide by the Tanzanian laws guiding the establishment, operation, and management of slaughterhouses. The study concludes that stakeholders were supporting the proposed development, due to outstanding positive impacts. The developer was committed to implement the environmental and social management and monitoring plan (ESMP) that would attend to mitigation measures about likely negative impacts on the development while at the same time enhancing positive impacts. It was recommended that the developer should adhere to good practices in all phases of the development by adopting effective ESMP according to the Tanzanian and international standards guiding operation and management of slaughterhouses.